Formation of Residential Space in a Multicultural Community: The Interaction of Customary Institutions and Community Leaders in Tri Rukun Village, Boalemo, Gorontalo - Asta Juliarman Hatta; Dara Fitriani; Nurnaningsih Nico Abdul (Jurnal Lingkungan Binaan Indonesia, 2026)
Multicultural communities in rural areas face challenges in maintaining social harmony while preserving cultural identity within residential environments. Tri Rukun Village in Boalemo Regency, Gorontalo, represents a multicultural settlement inhabited by Gorontalo, Balinese, and Minahasan communities living together within the same environment. This study aims to analyze the roles of customary institutions and community leaders in shaping residential adaptation strategies in Tri Rukun Village. A qualitative method with an ethnographic approach was employed to understand social, cultural, and spatial dynamics within the community. Data were collected through participant observation, in-depth interviews, and documentation, while data analysis used thematic coding and the Miles and Huberman interactive analysis model. The findings indicate that customary institutions play important roles in land distribution, housing arrangements, and spatial conflict resolution through deliberative mechanisms based on local wisdom. Community leaders contribute to planning, design, and post-occupancy evaluation processes. Residential adaptation does not eliminate cultural identity but instead produces architectural hybridization through modifications in building materials, spatial organization, and housing elements adapted to social and environmental needs.